Characterization of early cellular and molecular mechnism of newcastle disease virus AF2240-induced apoptosis in MCF-7 cells - Mohammed, Ghrici (2011)
Newcastle disease virus (NDV) is an oncolytic virus that has shown promising results in anti-tumor therapy. However, neither the mechanism of NDV oncolysis nor NDV induced apoptosis were fully understood. The main objective of this study was to elucidate the mechanism by which NDV AF2240 induced apoptosis and to identify the signal that triggered apoptosis in MCF-7 cells. The cytotoxicity of NDV AF2240 against MCF-7 cells was assessed first. The NDV induced apoptosis was detected and analyzed by flow cytometry. Then the time kinetics of NDV replication via RT-PCR amplification of NP gene and the time kinetics of apoptosis detection based on caspase-8 activation were compared. Caspase-8 activation and flow cytometry were used to investigate ultra-violet (UV) inactivated NDV induced apoptosis and cycloheximide treated NDV infected MCF-7 cells. This latter was also treated with Z-VAD-fmk and the titer of NDV progeny was determined by plaque forming unit assay. The co-localization of NDV antigens and apoptotic markers were analyzed by electron microscopic and dual staining assay. The involvement of mitochondrial mediated pathway was investigated via the detection of mitochondrial permeability transition pore assay opening activation. The involvement of NDV binding and sialic acid receptor in NDV AF2240 induced apoptosis was analyzed by antibody inhibition and neuraminidase assays. The whole NDV AF2240 HN gene was amplified and cloned into pDisplay expression vector. The HN expression was detected by indirect immunofluorescence and HN induced apoptosis was assessed by flow cytometry. There was a significant increase of cell death to 58.91% induced by increased NDV titer (p <0.0003). In the same manner, flow cytometry analysis revealed a significant increase of apoptotic cells to 63.94% induced by all NDV AF2240 titers (p < 0.0001). The results suggested that oncolysis might probably be mediated by apoptosis and that both oncolysis and apoptosis were NDV AF2240 dose dependent. Apoptosis did not affect NDV infectivity but the treatment of NDV infected MCF-7 cells with the broad caspase inhibitor Z-VAD-fmk had an inhibitory effect on NDV progeny production. Caspase-8 activation was detected at 2 hr pi while expression of NDV genes started late at 6 hr pi. UV inactivated NDV AF2240 induced an increase of apoptosis of 20 % obtained at 72 hr pi. Treatment of NDV infected MCF-7 cells with cycloheximide did not inhibit apoptosis induction. This means that NDV induced apoptosis might be NDV replication and protein synthesis independent. NDV AF2240 induced apoptosis was mediated by both death receptor and mitochondrial mediated apoptosis. The antibody inhibition assay showed a significant decrease of apoptotic cells obtained after treatment with anti-NDV AF2240 antibody (p < 0.0003). Neuraminidase treatment showed a significant decrease of the percentage of apoptotic cells with the increased amount of neuraminidase treatment (p< 0.0003). This inhibitory effect means that NDV induced apoptosis might be dependent on the binding of NDV to sialic acid receptor. The HN expression alone induced significant increase of apoptotic cells (p< 0.0001). HN induction of apoptosis was dose dependent. As a conclusion, NDV AF2240 induced apoptosis at the attachment step of NDV life cycle and that NDV HN glycoprotein is most probably responsible for NDV AF2240 induction of apoptosis. Our findings suggest that the use of NDV AF2240 as an anti-cancer agent can be more beneficial for cancer patients since the virus induced a faster tumor cell death which can be translated into faster elimination of tumor cells and a reduction or elimination of chances of metastasis occurrence. The possibility of NDV AF2240 to selectively replicate and spread within tumor cells will eventually reach all the tumor cells and kill them by apoptosis is another benefit for cancer patients. Alternatively recombinant NDV HN glycoprotein which has shown an oncolytic effect on tumor cells can be used as an anti-tumor tool. Recombinant HN has more advantages than the whole virus such as its efficiency is stable over long storage, ease of mass production and absence of virus escapes mutants. However, recombinant pDisplay-HN need additional engineering before it can be used as an anti-cancer tool in cancer patients.